Preemptive Chest Tube in Liver Transplantation – An Unconventional way to Reduce Morbidity. (July 2018) - Wiering, Leke; Ritschl, Paul; Sponholz, Felix; Brandl, Andreas; Aigner, Felix; Biebl, Matthias; Eurich, Dennis; Schmelzle, Moritz; Sauer, Igor; Kotsch, Katja; Pratschke, Johann; Öllinger, Robert
Abstract : Introduction: For various reasons, liver transplant recipients are frequently affected by pleural effusions in the immediate postoperative phase. High volume turn over and low serum albumin/protein due to reduced synthesis represent main risk factors. In addition, local irritation at the diaphragm leads towards fluid collection in the right hemi-thorax. The purpose of this study was to evaluate the prevalence of drainage requiring pleural effusions after liver transplantation (LTx) and to analyze post interventional complications. Methods: The years 2009 to 2016 were analyzed retrospectively for all patients, who underwent LTx. Pediatric recipients and combined liver/lung transplantations were excluded. The indication for pleural drainage was oxygenation problems or in case of atelectasis pneumonia prophylaxis. The observation period ended at postoperative day 10. Results: In the transplantation center Charité – Berlin 688 liver transplantations were performed in the investigated era. 375 out of 576 patients (62%) had at least one pleural drainage placed within the first 10 days after transplantation. Patients with a MELD score >20 were mostly affected (76% vs 54%, p < 0.01). Typically, drainages were performed at the ICU (60%) whereas the rest was done in the operating room at the time of transplantation (13, 5%), prior transplantation (9%), via CT puncture (0, 9%) or in the context of reoperations (9, 2%). 96% received a thoracic catheter on the right side presumably caused by local irritations, 4% had an isolated pleural drainage on the left side. 10 % required bilateral chest tubes. Due to liver-disease related pathophysiology one third of all patients needed pre interventional optimization of coagulation via thrombocytes, fresh frozen plasma or prothrombin complex concentrate. Out of 375 patients receiving an intercostal drain 14 (3, 7%) suffered from hemorrhage and 6 (1.6%) from pneumothorax requiring further medical treatment. According to Clavien-Dindo classifications 6 patients were II°, 11 patients IIIA° and 3 patients required surgery in ITN classified as IIIB°. In the investigated period mainly 2 types of chest tubes were used, the Pleurascan© via needle puncture or a surgical suction drainage (Bülau). No significant difference in aspect of bleeding complications was observed. Pneumothorax occurred in 2 of 24 single-punctures without tube installation (p=0, 028 compared to Bülau drainage 4/243). When comparing the time point/localization of the drainage placement a tendency towards less complications could be observed when performed during the transplantation as compared to the postoperative application on the ICU (1/68 (1, 5%) vs 18/236 (7, 6%); p=0.064). Conclusion: Pleural effusion, more frequent in patients with higher MELD, is a common complication after LTx requiring intervention in most cases. Routinely placed intraoperative chest tubes may reduce complications and avoid unnecessary coagulation products in high risk patients.